Live substrate positively affects root growth and stolon direction in the woodland strawberry, Fragaria vesca - Waters, Erica M.; Watson, Maxine A. (Frontiers in Plant Science, 2015)
Studies of clonal plant foraging generally focus on growth responses to patch quality once rooted. Here we explore the possibility of true plant foraging; the ability to detect and respond to patch resource status prior to rooting. Two greenhouse experiments were conducted to investigate the morphological changes that occur when individual daughter ramets of Fragaria vesca (woodland strawberry) were exposed to air above live (non-sterilized) or dead (sterilized) substrates. Contact between daughter ramets and substrate was prohibited. Daughter ramet root biomass was significantly larger over live versus dead substrate. Root:shoot ratio also increased over live substrate, a morphological response we interpret as indicative of active nutrient foraging. Daughter ramet root biomass was positively correlated with mother ramet size over live but not dead substrate. Given the choice between a live versus a dead substrate, primary stolons extended preferentially toward live substrates. We conclude that exposure to live substrate drives positive nutrient foraging responses in Fragaria vesca. We propose that volatiles emitted from by the substrates might be effecting the morphological changes that occur during true nutrient foraging.